2015
DOI: 10.3389/fneur.2014.00274
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Panax notoginseng Saponin Therapy for Acute Intracerebral Hemorrhage, Meta-Analysis, and Mini Review of Potential Mechanisms of Action

Abstract: Intracranial/intracerebral hemorrhage (ICH) is a leading cause of death and disability in people with traumatic brain injury (TBI) and stroke. No proven drug is available for ICH. Panax notoginseng (total saponin extraction, PNS) is one of the most valuable herb medicines for stroke and cerebralvascular disorders in China. We searched for randomized controlled clinical trials (RCTs) involving PNS injection to treat cerebral hemorrhage for meta-analysis from various databases including the Chinese Stroke Trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 137 publications
0
29
0
1
Order By: Relevance
“…Panax notoginseng saponins (PNS), the main effective ingredients of P. notoginseng, are clinically used in the prevention and treatment of cerebrovascular diseases in China, such as ischemic stroke (Zhang, Wu, & Zhang, 2015). So far, most scientists focus their research attention on the effects of PNS concerning blood dynamics invigoration, anti-thromboembolism, anti-coagulation, anti-hyperglycemia, antihyperlipidemia, anti-edema, and neroprotection (Xu et al, 2015) but ignoring the effect on BBB (brain microvasculature). What is more, previous report demonstrated that early BBB disruption might be a cause rather than a consequence of brain neuron injury in several cerebral disease (Shi et al, 2016).…”
mentioning
confidence: 99%
“…Panax notoginseng saponins (PNS), the main effective ingredients of P. notoginseng, are clinically used in the prevention and treatment of cerebrovascular diseases in China, such as ischemic stroke (Zhang, Wu, & Zhang, 2015). So far, most scientists focus their research attention on the effects of PNS concerning blood dynamics invigoration, anti-thromboembolism, anti-coagulation, anti-hyperglycemia, antihyperlipidemia, anti-edema, and neroprotection (Xu et al, 2015) but ignoring the effect on BBB (brain microvasculature). What is more, previous report demonstrated that early BBB disruption might be a cause rather than a consequence of brain neuron injury in several cerebral disease (Shi et al, 2016).…”
mentioning
confidence: 99%
“…Intracranial bleeding, edema and coagulopathy are major predictors of mortality and morbidity of TBI that still lacks of effective therapy [9,53,54]. YB and its major active ingredient Notoginseng saponins (PNS) have dual anti-hemorrhage and anti-hemostasis properties [19,55]. YB showed signi cantly better antibleeding e cacy (92•30%) than pantoloc (71•20%) in severe TBI-induced stress gastrointestinal bleeding and ulcer [21,22] and is more effective in controlling gastrointestinal tract in ammation in colitis model of in ammatory bowel disease (IBD), by suppressing pro-in ammatory cytokine expression (including TNFa, IL-12p40, and IL-17) and T-and B-lymphocytes, and but promoting intestinal epithelial wound-healing/repairing [56].…”
Section: Discussionmentioning
confidence: 99%
“…As always, patient safety should be a priority. There were systematic reviews supporting the effectiveness and safety of Notoginseng total saponins injections 67 and Naoxueshu oral solution 68 as add‐on treatment in patients receiving routine treatment for hypertensive intracranial hemorrhage. Injections containing Notoginseng total saponins include Xueshuantong and Xuesaitong; however, Xuesaitong injection is not recommended because of its instructions for use state that it is contraindicated in acute hemorrhagic stroke.…”
Section: Recommendationsmentioning
confidence: 99%